A rare case of Bordetella avium pneumonia complicated by Raoultella planticola - Lavrenko, Anna (John Wiley and Sons Inc., 2020)

(untitled) (Clin Case Rep)
Bordetella avium pneumonia immunocompromised the patient with subsequent complication by a rare opportunistic Raoultella planticola infection, which became a nosocomial pathogen in the healthcare setting.